How much professional literature do Australian librarians read? Disseminating information retrieval research results to Australian LIS professionals - Haddow, Gaby; Harvey, R. (Association for Library and Information Science Education, 2003)
This paper reports on an investigation into how the results of information retrieval research are disseminated to LIS (library and information science) professionals in Australia. It sets the scene by briefly noting the literature about the communication gap between research and practice. It then notes the most significant initiatives and activities aimed at fostering and promoting research within the Australian LIS community, and describes the investigation and its results.